Investigation of secondary structure evolution of micellar casein powder upon aging by FTIR and SRCD: consequences on solubility. (5th December 2017) - Nasser, Sarah; Hédoux, Alain; Giuliani, Alexandre; Le Floch‐Fouéré, Cécile; Santé‐Lhoutellier, Véronique; de Waele, Isabelle; Delaplace, Guillaume
Abstract: BACKGROUND: Synchrotron radiation circular dichroism (SRCD) and Fourier transform infrared (FTIR) spectroscopy were used to examine the conformation evolution of micellar casein (MC) powder during storage and to determine whether the spectral changes could be related to their solubility evolution. RESULTS: A loss in intensity of SRCD spectra as a function of storage time has been observed. Quantification of secondary structures revealed losses of α ‐helix content during storage. Moreover, a redshift of the amide I band in the FTIR spectrum was demonstrated during the storage and was interpreted as a rearrangement of the secondary structure of the protein, which is in line with the SRCD results. The qualitative results obtained by FTIR clearly support the quantitative evolution of the secondary structure obtained by the analysis of SRCD spectra. Principal component analysis (PCA) of FTIR spectra permits a good separation of samples according to the storage time. PCA shows that the evolution of secondary structures and solubility loss are closely linked. CONCLUSION: With the quantitative data provided by SRCD spectra, it was established that, whatever the storage conditions, a unique curve exists between loss of α ‐helix content and loss in solubility, showing that loss of α ‐helix content is a marker of solubility loss for the MC powders studied. © 2017 Society of Chemical Industry